Automated inertial feedback for half-pipe snowboard competition and the community perception - Harding, J. W.; Toohey, K.; Martin, D.; Mackintosh, C.; Lindh, A.; James, D. (The impact of technology on Sport II, 2007)
No scientific research has yet targeted the athletic performance aspects or subjective judging protocols associated with elite half-pipe snowboard competition. Recently however, sport scientists from the Australian Institute of Sport (AIS) initiated a video based analysis of key performance variables (KPVs) associated with elite half-pipe snowboard competition. The development of a preliminary automated feedback system based upon Micro-electrochemical Systems (MEMS) sensors such as tri-axial accelerometers and tri-axial rate gyroscopes, designed to calculate objective information on these sport specific KPVs was initiated in parallel. Although preliminary, the results may provide practical benefit for elite half-pipe snowboard training and current subjective judging protocols. In light of theorised implications, this paper investigated the perception and possible social impact of these concepts on the practice community. Data was collected via semi-structured, open ended interviews with nine subjects (six athletes,two coaches, and one judge) currently involved in elite half-pipe snowboard competition. This study revealed 6 dimensions and 20 sub-dimensions relating to the practice community`s perceptions of 3 major themes that emerged during interviews. The themes included: 1) State of the current subjectiv e judging system, 2) Automated feedback and objective judging system, and 3) Future direction of the sport. There was dominant negative perception of a proposed automated judging concept based solely on objective information unless the system integrates with the current subjective judging protocol and continues to allow athletic freedom of expression and the capacity for athletes to showcase individual style and flair in elite competition. The results of this study provide the practice community an initial public forum to describe its perceptions to future automated judging concepts, nominating them to be the primary determinants of change, technological or otherwise, within their sporting discipline.